Different Journeys: Supervisor Perspectives on Disciplinary Conceptual Threshold Crossings in Doctoral Learning - Wisker, Gina (Critical Studies in Teaching and Learning, 2023)
This article offers insights into supervisor awareness of conceptual threshold crossings in doctoral learning nuanced by researcher disciplines. First explored in undergraduate learning, threshold concepts highlight variation related to learning in the disciplines, identifying how realising the absolutely key concepts in disciplines causes troublesome and transformative learning (Meyer & Land, 2005). Building on work on undergraduate disciplinary threshold concepts, but focusing on research learning, particularly at doctoral level, conceptual threshold crossings have been identified (Kiley & Wisker, 2009), characterising significant stages in the learning journeys of doctoral candidates. At these stages, candidates evidence transformations in research learning. They cross-conceptual thresholds. There has to date, however, been little exploration of specific discipline-related stages at which doctoral candidates cross such conceptual thresholds. This new work focuses specifically on discipline-related practices and stages of conceptual threshold crossing in doctoral research learning and supervisors' awareness and support for work arising from this.